Autoantibodies associated with prenatal and childhood exposure to environmental chemicals in faroese children - Osuna, Christa E; Grandjean, Philippe; Weihe, Pál; El-Fawal, Hassan A N (Toxicological Sciences, 2014)
Methylmercury, polychlorinated biphenyls (PCBs), and perfluorinated compounds (PFCs) are ubiquitous and persistent environmental chemicals with known or suspected toxic effects on the nervous system and the immune system. Animal studies have shown that tissue damage can elicit production of autoantibodies. However, it is not known if autoantibodies similarly will be generated and detectable in humans following toxicant exposures. Therefore, we conducted a pilot study to investigate if autoantibodies specific for neural and non-neural antigens could be detected in children at age 7 years who have been exposed to environmental chemicals. Both prenatal and age-7 exposures to mercury, PCBs, and PFCs were measured in 38 children in the Faroe Islands who were exposed to widely different levels of these chemicals due to their seafood-based diet. Concentrations of IgM and IgG autoantibodies specific to both neural (neurofilaments, cholineacetyltransferase, astrocyte glial fibrillary acidic protein, and myelin basic protein) and non-neural (actin, desmin, and keratin) antigens were measured and the associations of these autoantibody concentrations with chemical exposures were assessed using linear regression. Age-7 blood-mercury concentrations were positively associated with titers of multiple neural- and non-neural-specific antibodies, mostly of the IgM isotype. Additionally, prenatal blood-mercury and -PCBs were negatively associated with anti-keratin IgG and prenatal PFOS was negatively associated with anti-actin IgG. These exploratory findings demonstrate that autoantibodies can be detected in the peripheral blood following exposure to environmental chemicals. The unexpected association of exposures with antibodies specific for non-neural antigens suggests that these chemicals may have toxicities that have not yet been recognized.